2021
DOI: 10.1002/hep4.1630
|View full text |Cite
|
Sign up to set email alerts
|

Protein Phosphatase 1 Regulatory Subunit 3B Genotype at rs4240624 Has a Major Effect on Gallbladder Bile Composition

Abstract: The protein phosphatase 1 regulatory subunit 3B (PPP1R3B) gene is a target of farnesoid X receptor (FXR), which is a major regulator of bile acid metabolism. Both PPP1R3B and FXR have been suggested to take part in glycogen metabolism, which may explain the association of PPP1R3B gene variants with altered hepatic computed tomography attenuation. We analyzed the effect of PPP1R3B rs4240624 variant on bile acid composition in individuals with obesity. The study cohort consisted of 242 individuals from the Kuopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The study detail and its characteristics have been reported elsewhere 78 , 79 and in Table S3 . The study included a total of 262 participants of the Kuopio Obesity Surgery (KOBS) study who underwent the Roux-en-Y gastric bypass surgery at Kuopio University Hospital, and from whom both detailed liver histology and RNA sequencing data were available.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study detail and its characteristics have been reported elsewhere 78 , 79 and in Table S3 . The study included a total of 262 participants of the Kuopio Obesity Surgery (KOBS) study who underwent the Roux-en-Y gastric bypass surgery at Kuopio University Hospital, and from whom both detailed liver histology and RNA sequencing data were available.…”
Section: Methodsmentioning
confidence: 99%
“…RNA sequencing libraries underwent 50-nucleotide long paired-end sequencing on Illumina HiSeq 2500 machine, followed by read alignment, normalization and differential expression analysis considering the technical and confounding factors (namely RIN, uniquely aligned reads %, 3’ bias, age, sex, and BMI) as described previously. 79 The gene level count values were normalized using a trimmed-mean of M values converted to count per million using edgeR 80 and inverse normal transformed. The study protocol was approved by the Ethics Committee of the Northern Savo Hospital District.…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA sequencing was performed for 175 liver samples from the current study population. Briefly, RNA sequencing libraries underwent 50-nucleotide long paired-end sequencing on Illumina HiSeq 2500 machine, followed by read alignment, normalization and differential expression analysis considering the technical and confounding factors (namely RIN, uniquely aligned reads %, 3’ bias, age, sex and BMI) as described previously [ 37 , 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…To explore the relevance of our findings to human NASH pathobiology, we analyzed MGP expression in RNAseq data of the Kuopio Obesity Surgery (KOBS) clinical study. 19 Hepatic MGP expression was found to be significantly correlated with fibrosis stage in both female (r ¼ 0.156; P ¼ .036) (Figure 1D) and male patients (r ¼ 0.262; P ¼ .002) (Figure 1D). MGP expression was significantly increased in the livers of patients with NASH compared with non-NASH subjects (healthy or simple steatosis) (P ¼ .021).…”
mentioning
confidence: 89%
“…The KOBS study was previously described. 19 The current study included 262 subjects with liver histology (55.7% without and 44.3% with different stages of fibrosis) and RNA sequencing data. Liver biopsies were obtained with ultrasonic scissors during the laparoscopic Roux-en-Y gastric bypass surgery.…”
Section: Human Nash Study and Rna Sequencingmentioning
confidence: 99%